The development of a fast response measurement system for use in turbomachinery applications - Crowther, Shamal Mena (2018)
Improvements in the efficiency of power generation via turbomachinery are essential in order to reduce greenhouse gas emissions throughout the world. Advancements in measurement techniques are therefore crucial to understanding the main areas of energy loss in turbines and compressors. This thesis presents a novel system which allows that loss to be characterised using fast response, 3-D measurements of the pressure field within industrial scale rigs. Turbulent energy dissipation rates give an insight into where useable energy is lost from. To gain an insight into such rates, measurement techniques must be able to take data in all three dimensions simultaneously at high sampling rates, usually over 50 kHz. Traditional methods of flow characterisation such as optical techniques and pneumatic pressure probes are unable to capture the rapid fluctuations in pressure and velocity which lead to energy loss from the turbomachine. A new system was therefore designed and implemented into a 6-stage compressor rig to take fast response measurements at sampling frequencies up to 100 kHz behind the last stage stator. A fast-response 5-sensor pressure head, acquired from Kulite Semiconductor Products Inc, has been embedded into a bespoke stem to allow turbulence measurements in a range of turbomachinery applications. The five-sensor (5S) probe was calibrated for pressure sensitivity as well as aerodynamically to give total and static pressure along with velocity magnitude and direction. Individual sensors were calibrated and characterised at temperatures within a range of 200C and 500C, which corresponds to the conditions found within the final application. The probe was also used in a vortex shedding experiment where alternative eddies were detected from the 5S probe measurements in both the time and frequency domain. The aerodynamic calibration of the 5S probe consists of exposing the probe sensors to a range of flow angles in order to map their response between ±200 in both the yaw and pitch directions. This results in four non-dimensional coefficients, two to represent pressure and two to signify the flow angles. A linear interpolation method was written and implemented to deduce pressure and flow angles from experimental query points and the calibration data. The linear interpolation was used as an alternative to the standard surface fit method, where the calibration data is expressed as system of polynomial equations. It was found that the linear method was applicable to the interpolation of flow angles and gave a reduction in computation time of the order of 104. The total and static pressure values do however require the more tried and tested polynomial interpolation method due to the need for higher order interaction terms in the surface fit equation describing the terms. The fully calibrated 5S probe was then implemented into a 6-stage industrial scale rig where it acquired fast response pressure data from the flow field at the exit of the last stage vane. The data was processed to give time resolved, 3-D measurements of total and static pressure, flow angle and velocity. Due to the simultaneous capture of data from all 5 sensors, the resulting velocity vectors can be decomposed into their mean and periodic components to obtain values of energy loss from the turbomachine. The acquisition of such data from an industrial rig marks a novel advancement in the area of turbomachinery flow characterisation and the use of the 5S probe in a range of applications will begin to fulfil the need for a database of fast response data from chaotic and turbulent flow fields.